Wokół układu Piłsudski-Petlura. Porozumienie w świetle publikacji wybranych tytułów polskiej prasy codziennej - Korzeniowski, Mariusz (Przegląd Wschodnioeuropejski, 2023)
The present study analyzes the reaction of the subjectively selected titles of the daily Polish press to the signing of the Pilsudski-Petlura agreement. The article examines the consequences of the pact for the concerned parties and the significance of the treaty for the formation of the relations between the Second Polish Republic and Bolshevik Russia, and thus for the Polish government’s Eastern policy. The article also explores the extent of the publicists’ knowledge of the course of the talks between Poland and the Ukrainian People’s Republic.